Local Public Entrepreneurship and Judicial Intervention in a Euro-American and Global Perspective - Christian Iaione (Washington University Global Studies Law Review, 2008)
In this Article, I present local public entrepreneurship as a windfall of the right to local self-government. In Part II, I discuss the competing scholarship on the role local governments take in competing with each other by creating incentives to entice citizens and businesses into their jurisdictions. Then, in Part III, I present the concept of local public entrepreneurism and detail how local governments utilize such activism in competition with other governments.
Keywords: Globalization; Economic development; Entrepreneurship; Judicial power